Antenatal Diagnosis of a Partial Atrioventricular Canal with Ebstein's Anomaly - Gerald Laforest; Jean-Bernard Selly; Gilbert Dubois; Bernard Kreitmann; Yael Levy (MDPI AG, 2021)
The simultaneous occurrence of an atrioventricular canal defect (AVCD) and Ebstein's anomaly is extremely rare, occurring in less than 0.5% of all patients with AVCD. Only 22 cases are described in the literature. This patient's antenatal diagnosis of both Ebstein's anomaly and partial AVCD was made at 25 weeks of gestation. The delivery was organized in a tertiary center. The initial neonatal course was difficult but with adequate treatment, a rapid improvement allowed for a gap of almost 2 years before a complete surgical repair including a cone tricuspid plasty. To our knowledge, this is the first case of antenatal diagnosis, with carefully tailored delivery, neonatal care and subsequent follow-up before indication for successful surgery.